Eksplorasi Etnomatematika Konsep Geometri dan Perbandingan pada Makanan Tradisional Wingko Babat - Salsabila Nur Aini; Annafi Awantagusnik (Universitas Ma'arif Lampung, 2025)
This study aims to explore the concept of ethnomathematics contained in the traditional food Wingko Babat, particularly in terms of geometry and comparison. As part of Indonesia's cultural heritage, Wingko Babat not only has historical and culinary value, but also contains relevant mathematical elements that can be used as a medium for contextual learning. This study uses a qualitative research method with an ethnographic approach, namely by conducting interviews and direct observations of the geometric shapes of the surface and space, as well as the ratio of ingredients in the making of Wingko Babat. The results show that Wingko Babat, which is shaped like a block, can be used to explain geometric concepts such as surface area and volume. In addition, the composition of ingredients in the Wingko Babat-making process also contains mathematical values in the form of ratios, comparisons, and proportions. This study proves that traditional foods can serve as a means of contextual mathematics learning, while strengthening the connection between local culture and modern education.